Comparative Analysis of Onsite and Online Testing at Universidad Nacional Mayor de San Marcos - Pereyra Salazar, Jorge Antonio (2024)
The research shows the analysis of the means and standard deviations of the scores obtained in the last eight tests at the Centro Preuniversitario (Cram School) of the Universidad Nacional Mayor de San Marcos (UNMSM) of Peru taken onsite, before the COVID-19 pandemic, versus the eight subsequent tests during the pandemic, after the digitalization of admission processes. The result of this analysis establishes that the digitalization of the process did not cause any significant difference in the results of the onsite and online processes. The results showed that, in the absence of these differences, it is thought that the process was adequately digitalized since the behavior of the online and onsite test scores were similar.